Effect of Work Discipline and Job Satisfaction on Employee Performance at the Pratama Gotong Royong Clinic Surabaya - Luckna Maudy Syafira; Bayu Arlangga Putra; Hermien Tridayanti; Elok Damayanti (Journal of World Conference (JWC), 2021)
This study aims to determine the effect of work discipline and job satisfaction on employee performance at the Pratama Gotong Royong Clinic in Surabaya. The approach used in this research is quantitative. Respondents in this study were all employees of the Pratama Gotong Royong Clinic in Surabaya with a total of 40 respondents. The source of this research data was obtained by distributing questionnaires to respondents to obtain primary data. The analysis technique used is a multiple linear analysis technique which aims to determine how much influence the variables of Work Discipline and Job Satisfaction (t-test) have on employee performance. Meanwhile (f-test) is used to test whether this research is feasible or not to be used for this research. The results of the study stated that the variables of Work Discipline and Job Satisfaction had a significant effect on employee performance.